Synthesis and characterization of poly-L-lysine-grafted silica nanoparticles synthesized via NCA polymerization and click chemistry - Kar, Mrityunjov; Vijayakumar, P. S.; Bhagavatula L. V. Prasad; Sen Gupta, Sayam (Langmuir, 2010)
Polypeptide polymer-grafted silica nanoparticles are of considerable interest because the ordered secondary structure of the polypeptide grafts imparts novel functional properties onto the nanoparticle composite. The synthesis of poly-L-lysine-grafted nanoparticles would be of particular interest because the high density of cationic charges on the surface could lead to many applications such as gene delivery and antimicrobial agents. In this work, we have developed a ``grafting-to'' approach using a combination of NCA polymerization and ``click chemistry'' to synthesize poly-L-lysine-grafted silica nanoparticles with a high graft density of 1 chain/nm(2). The covalent attachment of poly-L-lysine to silica nanoparticles (PLL-silica) was confirmed using a variety of techniques such as C-13 CP MAS NMR, TGA, and IR. This methodology was then extended to graft poly-L-lysine-b-poly-L-leucine copolymer (PLL-b-PLLeu-silica) and poly-L-benzylglutamate (PLUG silica) onto silica nanoparticles. All of these polypeptide-grafted nanoparticles show interesting aggregation properties in solution. The efficacy of PLL-silica and PLL-h-PLLeu-silica as antimicrobial agents was tested on both gram-negative B. cull and grain-positive Bacillus subtilis.